Career success: Analysis and development of career opportunities in students - Pshembayeva, Elmira; Pfeyfer, Nellie; Uaikhanova, Meruyert; Bubenchikova, Anastasiia (Frontiers in Education, 2022)
Effective implementation and development of the career development programmes determine the economic growth of countries. The research aims to discuss and analyse the characteristics and elements of the students' career opportunities. The results help the scholars select the proper type of analysis and appropriate tools to examine the elements of career opportunities. The sample consisted of 102 third and fourth year students from NJSC Toraighyrov University. The following methods and criteria were used to analyse the initial stage of the student career development: emotional intelligence (based on the methodology proposed by J. N. Hall), communication skills (Test of communication skills by L. Mikhelson), self-assessment (S. A. Budassi’s method of self-assessment), career value orientations (Edgar Schein's Career Anchors), motivation for success (The Questionnaire by T. Ehlers). The surveys were conducted using Google Forms. The results helped to identify the characteristics and elements of the students' career opportunities. The data collected at NJSC Toraighyrov University of the Republic of Kazakhstan show that 35% of students have a low level of emotional intelligence, 47% have addictive behaviours during communication, 31% of respondents have low self-esteem, lack of motivation for success was identified in 18% of students. Only a small number of students could clearly define their career orientations regarding Lifestyle Integration, Challenge and Management. The research suggests that it is important to introduce career development programmes that empower students and encourage them to build professional career paths in the future. Used as a learning framework, the Career coaching programme helps to design, develop, assess and implement each element of the career opportunities. The implementation advantages of the Career coaching programme for students as part of the educational process are discussed in the present research. The programme Career coaching will develop awareness and advance careers among graduate students. Moreover, it will provide a guideline for the first steps towards developing a successful career path.